COMMUNITY EMPOWERMENT IN MANAGING WASTE THROUGH TAKAKURA TRAINING - suzi soliati (IKIP Siliwangi Bandung, 2019)
Household waste from approximately three million residents of the city of Bandung, every day reaches approximately 2000 tons or reaches 6195 cubic meters consisting of 65% organic waste, 10% paper, 2% plastic, 1% glass, 1% cloth, 8% metal and other 13%. In terms of waste management, each region has the potential that if managed and utilized properly will help improve their quality of life. Society has an important role in efforts to empower the community, because society is the subject of empowerment. The RT.04 RW 011 administrator at Kompleks Pasirjati Bandung was moved to empower the community in managing household waste through Takakura / composting training. This training aims to empower the community in reducing household waste and in maintaining environmental cleanliness through environmentally friendly waste management. The training participants were residents in the Kompleks Pasirjati neighborhood RT.04, RW. 011 Bandung City, 22 people.